Evaluation of the impact and relevance of different energy related renovation measures on selected Case Studies (Annex 56) - Almeida, Manuela Guedes de (2017)
To promote energy efficient buildings, with low energy consumption and energy generation onsite, innovative renovation projects are needed that can act as forerunners and inspiration but also serve as best practice examples for the expert audience and the general public. Within this IEA EBC Annex 56 project, six different Case Studies from six European countries were compiled and analysed . The Case Studies are both residential and non-residential buildings, which serve as model projects for renovations in each individual country. The specific aim of the case study activity of this IEA EBC Annex 56 project is to provide significant and useful feedback from practice on a scientific basis.